2018
DOI: 10.1371/journal.pcbi.1006010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic enzyme cost explains variable trade-offs between microbial growth rate and yield

Abstract: Microbes may maximize the number of daughter cells per time or per amount of nutrients consumed. These two strategies correspond, respectively, to the use of enzyme-efficient or substrate-efficient metabolic pathways. In reality, fast growth is often associated with wasteful, yield-inefficient metabolism, and a general thermodynamic trade-off between growth rate and biomass yield has been proposed to explain this. We studied growth rate/yield trade-offs by using a novel modeling framework, Enzyme-Flux Cost Min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 67 publications
2
83
0
Order By: Relevance
“…However, other traits influence survival and reproduction and hence carrying capacity, generation time and asymptotic body mass. If we were to extend our size‐structured life‐history models to include other traits such as metabolic rate (Wortel et al ) and energy budgets (Smallegange et al ), we may expect the variance in the scatter around Fig. to decline as we search for multi‐trait structured life‐history strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, other traits influence survival and reproduction and hence carrying capacity, generation time and asymptotic body mass. If we were to extend our size‐structured life‐history models to include other traits such as metabolic rate (Wortel et al ) and energy budgets (Smallegange et al ), we may expect the variance in the scatter around Fig. to decline as we search for multi‐trait structured life‐history strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of kinetic descriptions of transcriptional and translational events into kinetic parameterization procedures would allow for the decoupling of enzyme concentration and elementary kinetic parameters. As an alternative to direct description of protein synthesis events in the cell, protein cost studies have shown that cellular enzyme concentration can be reasonably predicted using kinetic rate expressions for metabolic reactions [95,96]. It may, therefore, be possible to use kinetic rate expressions for enzyme catalyzed reactions directly to characterize changes in enzyme level across conditions rather than kinetic expressions for transcription and translation.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the context of maximum growth rate prediction of microbial cells, there are theoretical results that support the existence of such optimal rates defined by a single EFM . More recently, enzyme‐flux cost minimization (EFCM) has been proposed to rationally explain the trade‐offs between growth rate and yield(s) based on the ECM framework …”
Section: Constraint‐based Optimization Methods For Pathway Designmentioning
confidence: 99%
“…[70,71] More recently, enzyme-flux cost minimization (EFCM) has been proposed to rationally explain the trade-offs between growth rate and yield(s) based on the ECM framework. [72] Application of ECM has been mostly focused on evaluating alternative metabolic pathways fulfilling known biological functions such as carbon assimilation [20] and efficient carbon conversions. [56,57] In both cases, metabolic conditions defined by the allowable metabolite concentrations, as well as pH and ionic strength, played critical roles in determining the most "economical" pathway choice.…”
Section: Pathways With Minimum Enzymatic Costmentioning
confidence: 99%